Characterization of the XIAP-Inhibiting Proanthocyanidin Fraction of the Aerial Parts of Ephedra sinica - Schäfer, S.; Salcher, S.; Seiter, M.; Ranninger, C.; Möst, M.; Obexer, P.; Huber, C. G.; Ausserlechner, M. J.; Schwaiger, S.; Stuppner, H. (Planta Medica, 2016)
The X-linked inhibitor of apoptosis protein is a cellular protein that inhibits the activity of mammalian caspases and promotes resistance to apoptosis. The ethanol extract of the aerial parts of Ephedra sinica has been identified to possess inhibitory activity of the X-linked inhibitor of apoptosis protein by an in vitro fluorescence polarization assay using the BIR3 domain of the X-linked inhibitor of apoptosis protein. Bioactivity-guided fractionation identified proanthocyanidin-enriched fractions as the active principles. The most active fraction showed an IC50 value of 27.3 µg/mL (CI95: 25.9–28.9 µg/mL) corresponding to 9.6 µM (CI95: 9.1–10.1 µM) calculated by the use of the determined average molecular weight of 2853.5. Samples were analyzed by a thiolytic degradation/HPLC-MS assay, UHPLC-HRMS, and 1D NMR.The thiolytic degradation/HPLC-MS assay revealed a mean degree of polymerization of 9.5 ± 0.2 units (calculated average MW 2853.5) for the active fraction and 11.4 ± 0.6 units (calculated average MW 3437.0) for the most related inactive fraction. Chemical characterization identified (epi)gallocatechin (76.6 ± 1.0 % active; 80.7 ± 2.7 % inactive sample) and (epi)catechin units as building blocks. Interestingly, the investigated proanthocyanidins turned out to be a complex mixture of double linked A-type (binding 2-O-7″, 4–6″) and single linked B-type units.This study identified oligomeric proanthocyanidins as active principles of E. sinica in vitro by a fluorescence polarization assay and via protein fragment complementation analysis.
Keywords: Ephedra sinica; Ephedraceae; proanthocyandin; XIAP; fluorescence polarization